Gambaran Kompetensi Kepribadian Instruktur pada Pembelajaran Pelatihan Menjahit di Panti Sosial Bina Remaja Harapan Kota Padang Panjang - Nurlaila Safitri; Wisroni Wisroni; Solfema Solfema (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2018)
This research is motivated by the high participation of citizens of learning in following the learning of sewing. This is due to the Instructor's personality competence in teaching. The purpose of research to see the Competence Personality Instructor training tailoring in the Social Institution Bina Remaja Harapan Padang Panjang. This research uses quantitative descriptive approach. Population 40 people while the sample amounted to 30 people, namely 69% of the population, sampling technique is cluster random sampling. Technique of collecting data through questionnaire. The result of the Instructor personality competence picture is seen from; (1) acting in accordance with the norm, (2) being honest, noble and exemplary, (3) steady person, (4) having a high work ethic with very good classification of percentage can be categorized. Conclusion Instructors have a high personality competence from aspects of norms, personal noble character and be role model, personal steady, and has a work ethic. Suggestion of this research for Instructor to increase personality competence as an educator and professional trainer.Keywords: Personality Competency, Instructors, Learning Sewing